Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

a) 2/7+-3/8+11/7+1/3+1/7+5/-8
=(2/7+11/7+1/7)+(3/8+-5/8)+1/3
=2+2+1/3
=4+1/3
=13/3
b) -3/8+12/25+5/-8+2/-5+13/25
=(-3/8+-5/8)+(12/25+13/25)+-2/5
=-1+1+-2/5
=0+-2/5
=-2/5
c)7/8+1/8*3/8+1/8*5/8
=7/8+1/8*(3/8+5/8)
=7/8+1/8*1
=7/8+1/8
=1
a) 2/7+-3/8+11/7+1/3+1/7+5/-8
=(2/7+11/7+1/7)+(3/8+-5/8)+1/3
=2+2+1/3
=4+1/3
=13/3
b) -3/8+12/25+5/-8+2/-5+13/25
=(-3/8+-5/8)+(12/25+13/25)+-2/5
=-1+1+-2/5
=0+-2/5
=-2/5
c)7/8+1/8*3/8+1/8*5/8
=7/8+1/8*(3/8+5/8)
=7/8+1/8*1
=7/8+1/8
=1

bài 1b)
\(8\frac{1}{14}-6\frac37\)
C1:\(\frac{113}{14}-\frac{45}{7}\) =\(\frac{113}{14}-\frac{90}{14}=\frac{23}{14}\)
C2:\(8\frac{1}{14}-6\frac37=\left(8-6\right)+\left(\frac{1}{14}-\frac37\right)=2+\left(\frac{1}{14}-\frac{6}{14}\right)\)
\(=2+\frac{-5}{14}=\frac{28}{14}-\frac{5}{14}=\frac{23}{14}\)
bài 1 c)\(7-3\frac67\)
C1:\(\) \(7-3\frac67=7-\frac{27}{7}=\frac{49}{7}-\frac{27}{7}=\frac{22}{7}\)
C2:\(7-3\frac67=\left(7-3\right)-\frac67=4-\frac67=\frac{28}{7}-\frac67=\frac{22}{7}\)

a. \(1\frac{5}{7}\)-\(\frac{9}{7}\)*\(\frac{16}{9}\)
=\(\frac{12}{7}\)-\(\frac{16}{7}\)
=\(\frac{-4}{7}\)
b. \(\frac{-5}{8}\):\(\frac{1}{4}\)-\(\frac{6}{13}\)*4+\(\frac{3}{8}\)
=\(\frac{-5}{8}\cdot\)4-\(\frac{6}{13}\)*4+\(\frac{3}{8}\)
=4*(\(\frac{-5}{8}\)-\(\frac{6}{13}\))+\(\frac{3}{8}\)
=4*\(\frac{-113}{104}\)+\(\frac{3}{8}\)
=\(\frac{-113}{26}\)+\(\frac{3}{8}\)
=\(\frac{-413}{104}\)
c.( \(\frac{3}{8}\)+\(\frac{-1}{4}\)-\(\frac{5}{12}\)):\(\frac{1}{3}\)
=\(\frac{-7}{24}\)*3
=\(\frac{-7}{8}\)
Học tốt

a: \(=-9+\left\{-52:9\right\}=-9+\dfrac{-52}{9}=-\dfrac{133}{9}\)
b: \(=\dfrac{17}{7}+\left(\dfrac{-76}{63}\right):15\)
\(=\dfrac{17}{7}-\dfrac{76}{63}\cdot\dfrac{1}{15}=\dfrac{317}{135}\)
e: \(=\dfrac{-5}{13}\cdot\dfrac{7}{3}-\dfrac{2}{7}\cdot\dfrac{8}{13}+\dfrac{5}{13}\cdot\dfrac{1}{7}\)
\(=\dfrac{5}{13}\left(-\dfrac{7}{3}+\dfrac{1}{7}\right)-\dfrac{2}{7}\cdot\dfrac{8}{13}\)
\(=\dfrac{5}{13}\cdot\dfrac{-46}{21}-\dfrac{16}{91}=\dfrac{-278}{273}\)

\(\frac37+\frac{5}{13}+\frac{4}{13}\)
=\(\frac37+\left(\frac{5}{13}+\frac{4}{13}\right)\)
=\(\frac37+\frac{9}{13}\)
=\(\frac{39}{91}+\frac{63}{91}\)
=\(\frac{102}{91}\)
\(\left(\frac38+\frac{-3}{4}+\frac{7}{12}\right):\frac56+\frac12\)
=\(\left(\frac{9}{24}+\frac{-18}{24}+\frac{7}{24}\right)\times\frac65+\frac12\)
=\(\frac{5}{24}\times\frac65+\frac12\)
=\(\frac14+\frac12\)
=\(\frac14+\frac24\)
=\(\frac34\)

Bài 1:
a) Ta có: \(\frac{8}{40}+\frac{-4}{20}-\frac{3}{5}\)
\(=\frac{1}{5}+\frac{-1}{5}-\frac{3}{5}\)
\(=\frac{-3}{5}\)
b) Ta có: \(\frac{-7}{12}+\frac{-2}{12}-\frac{-3}{36}\)
\(=\frac{-7}{12}+\frac{-2}{12}-\frac{-1}{12}\)
\(=\frac{-9+1}{12}=\frac{-8}{12}=\frac{-2}{3}\)
c) Ta có: \(\left(\frac{1}{6}+\frac{-4}{13}\right)-\left(-\frac{17}{6}-\frac{30}{13}\right)\)
\(=\frac{1}{6}+\frac{-4}{13}+\frac{17}{6}+\frac{30}{13}\)
\(=3+2=5\)
d) Ta có: \(-\frac{-5}{4}+\frac{7}{4}-\frac{-11}{7}+\frac{2}{7}\)
\(=\frac{5}{4}+\frac{7}{4}+\frac{11}{7}+\frac{2}{7}\)
\(=3+\frac{13}{7}=\frac{21}{7}+\frac{13}{7}=\frac{34}{7}\)
e) Ta có: \(-\frac{1}{8}+\frac{-7}{9}+\frac{-7}{8}+\frac{6}{7}+\frac{2}{14}\)
\(=-1+1+\frac{-7}{9}\)
\(=-\frac{7}{9}\)
f) Ta có: \(\frac{-2}{9}-\frac{11}{-9}+\frac{5}{7}-\frac{-6}{-7}\)
\(=\frac{-2-\left(-11\right)}{9}+\frac{5-6}{7}\)
\(=1+\frac{-1}{7}=\frac{7}{7}+\frac{-1}{7}=\frac{6}{7}\)

a. \(\frac{-3}{7}+\frac{15}{26}-\left(\frac{2}{13}-\frac{3}{7}\right)=\frac{-3}{7}+\frac{15}{26}-\frac{2}{13}+\frac{3}{7}=\frac{15}{13.2}-\frac{2}{13}=\frac{15}{13.2}-\frac{2.2}{13.2}=\frac{15-4}{26}=\frac{11}{26}\)
C. \(\frac{-11}{23}.\frac{6}{7}+\frac{8}{7}.\frac{-11}{23}-\frac{1}{23}=\frac{1}{23}.\left(-11.\frac{6}{7}-11.\frac{8}{7}-1\right)=\frac{1}{23}.\left(-22-1\right)=\frac{1}{23}.\left(-23\right)=-1\)
Tính :
a) \(\frac{1}{6}.\frac{9}{-8}.\left(-\frac{12}{11}\right)=\frac{1.9.\left(-12\right)}{6.\left(-8\right).11}=\frac{1.3.3}{2.2.11}=\frac{9}{44}\)
b) \(\frac{1}{8}.\frac{-3}{7}+\frac{1}{8}.\frac{-4}{7}\)
\(=\frac{1}{8}.\left(-\frac{3}{7}+\frac{-4}{7}\right)\)
\(=\frac{1}{8}.\frac{-7}{7}=\frac{1}{8}.\left(-1\right)\)
\(=-\frac{1}{8}\)
c) \(\frac{7}{13}.\frac{3}{-5}+\frac{6}{13}.\frac{-3}{5}\)
\(=-\frac{3}{5}.\left(\frac{7}{13}+\frac{6}{13}\right)\)
\(=-\frac{3}{5}.\frac{13}{13}=-\frac{3}{5}.1\)
\(=-\frac{3}{5}\)
a, \(\frac{1}{6}.\frac{9}{-8}.\frac{-12}{11}\)
\(\Rightarrow\frac{9}{8}.\frac{2}{11}\)
\(\Rightarrow\frac{9}{4}.\frac{1}{11}\)
\(\Rightarrow\frac{9}{44}\)
b,\(\frac{1}{8}.\frac{-3}{7}+\frac{1}{8}.\frac{-4}{7}\)
\(\Rightarrow\frac{-3}{56}-\frac{1}{2}.\frac{1}{7}\)
\(\Rightarrow\frac{-3}{56}-\frac{1}{2}.\frac{1}{7}\)
\(\Rightarrow\frac{-3}{56}-\frac{1}{14}\)
\(\Rightarrow\frac{-1}{8}\)
c,\(\frac{7}{13}.\frac{3}{-5}+\frac{6}{13}.\frac{-3}{5}\)
\(\Rightarrow\frac{-21}{65}-\frac{18}{65}\)
\(\Rightarrow\frac{-3}{5}\)